Energy Use Pattern in Relation to Watershed Management - a Case Study in Sillwalik Foothill Village - Arya, Swarn Lata; Samra, J. S. (Indian Forester, 1998)
An attempt was made in the present paper to study the effect of a watershed management project on energy consumption pattern in Shiwalik foothill village in Haryana State. The project helped the villagers to reduce their dependency on fuel wood for domestic use and thereby reduction in indiscriminate cutting of trees. This happened because of increase in dung production in the village as a result of stall feeding of animals and change in the composition of animal population in favour of buffaloes from goats. Grazing the animals in the community forest area was stopped voluntarily after the formation of Hill Resource Management Society. Besides analysing the family fuel wood requirement on the basis of socio-economic parameters using multiple regression approach, the paper has also outlined the potentials of developing the use of gobar gas for reducing the dependency on commercial as well as conventional non-commercial sources of energy.